2021
DOI: 10.32535/jicp.v4i1.1129
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Willingness to Engage in NeWOM and Brand Attitudes on Purchase Intention Mediated by Company Mitigation Responses: A Case Study of The Energy Drink in Central Java

Abstract: The aims of this study were to determine the impact of willingness to engage in negative eWOM from and brand attitudes on purchase intention of Joss extra energy drink products mediated by mitigation responses of companies in Central Java. The method in this is descriptive and verification. This study used a purposive random sampling technique with a total sample of 167 respondents. The results of this study indicate that the Brand Attitude variable has nonsignificant effect on Repurchase Intention, the negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…For instance, the consumer might have a favorable brand experience with the brand. This is in line with Hersetyawati, Arief, Furinto, and Saroso (2021), who state that WOM is affected not only the customer's purchase but also the company. Brand experience is an evaluative assessment by consumers regarding how the identity, design, package, functionality, and communication style of the brand can influence their cognition, sense, and feeling (Brakus, Schmitt, & Zarantonello, 2009).…”
Section: Brand Experience and Womsupporting
confidence: 87%
“…For instance, the consumer might have a favorable brand experience with the brand. This is in line with Hersetyawati, Arief, Furinto, and Saroso (2021), who state that WOM is affected not only the customer's purchase but also the company. Brand experience is an evaluative assessment by consumers regarding how the identity, design, package, functionality, and communication style of the brand can influence their cognition, sense, and feeling (Brakus, Schmitt, & Zarantonello, 2009).…”
Section: Brand Experience and Womsupporting
confidence: 87%
“…A study examines the effect of brand loyalty on Therefore, the brand recommendation is one of the most desired outcomes of brand loyalty (Hersetyawati, 2021;Japutra, 2021). From these various opinions and research, it can be concluded that when a consumer has a good experience with a brand, the consumer will feel that the brand provides added value and ultimately love the brand.…”
Section: Influence Brand Loyalty With Positive Wommentioning
confidence: 99%
“…Companies must also recognize that while parasocial relationships can play a significant role in building brand advocacy, they need to exercise caution in managing these relationships and ensuring their alignment with overall brand values and image (Ha, 2023;Purnamaningsih & Rizkalla, 2020). A positive parasocial relationship can lead to increased brand loyalty and advocacy (Reinikainen et al, 2020), whereas a negative relationship can adversely affect a brand's reputation (Hersetyawati, Arief, Furinto, & Saroso, 2021;Naidoo & Abratt, 2018). Therefore, companies must attentively assess the quality of the parasocial relationships they establish and regularly evaluate their effectiveness in achieving their marketing goals.…”
Section: Introductionmentioning
confidence: 99%